Effective Employee Management in Times of Organizational Transformation - Widjaja, Purna (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study examines the effectiveness of employee management strategies during organizational transformation, focusing on their impact on agility, resilience, and success. Research Design and Methodology: Utilizing a qualitative approach, the research analyzes existing literature to explore the dynamics of employee management in transformative contexts. Data is gathered from academic journals, books, and reputable online sources, employing an exploratory and interpretive framework. Findings and Discussion: The findings emphasize the critical role of aligning human resource practices with organizational goals to enhance employee engagement and organizational competitiveness. Agile performance management, characterized by flexibility and continuous feedback, is identified as crucial for adaptability. The importance of proactive talent development and leveraging technology in HR practices is also highlighted, supporting a skilled and adaptable workforce. Implications: The study suggests that organizations need to implement comprehensive employee management strategies that resonate with their strategic goals to navigate transformation effectively. It advocates for the integration of technology to improve HR functionalities, ultimately fostering a resilient and innovative organizational culture.